A mechanistic understanding of oxygen isotopic changes in the Western United States at the Last Glacial Maximum. (15th December 2021) - Tabor, Clay; Lofverstrom, Marcus; Oster, Jessica; Wortham, Barbara; de Wet, Cameron; Montañez, Isabel; Rhoades, Alan; Zarzycki, Colin; He, Chengfei; Liu, Zhengyu
Abstract: At the Last Glacial Maximum (LGM), records suggest drier conditions in the northwest United States and wetter conditions in the southwest United States relative to present-day as well as widespread changes in the isotopic composition of water. However, the mechanisms responsible for these changes remain ambiguous. Here, we explore differences in western United States hydroclimate between the LGM and preindustrial with a water isotope tracer enabled Earth System Model. We then use proxy forward models to compare simulated and recorded δ 18 O in speleothems. We find that the pattern of hydroclimate response in the western United States at the LGM relates to a combination of 1) increased frequency and southward shifted wintertime extratropical cyclones in the North Pacific, 2) greater rainout of moisture as it moves over the continent, and 3) reduced evaporation in the cooler LGM climate. The simulated lower δ 18 O of precipitation at the LGM relates predominantly to an increase in cool season moisture removal efficiency, with a secondary contribution from relatively more cool season precipitation. Both surface temperatures and North American ice sheets contribute to these hydroclimate changes at the LGM. Comparisons between δ 18 O from proxy forward models and speleothem records in the western United States show general agreement at the LGM, with increasing depletion moving towards the continental interior. This study highlights the similarities and differences between hydrologic and δ 18 O changes at the LGM and emphasizes the utility of model-proxy comparison for interpretation. Highlights: iCESM and forward proxy models used to understand δ 18 O changes in western US at LGM. North Pacific storms contribute to southward shift of moisture in western US at LGM. Lower δ 18 O of precipitation in western US at LGM due largely to greater moisture removal efficiency. Forward proxy model outputs generally agree with speleothem records. Combination of climate and proxy models improve understanding of speleothem δ 18 O.